Orbital Forming of Tailored Blanks for Industrial Application - Hetzel, Andreas; Lechner, Michael (Sheet Bulk Metal Forming, 2021)
The efficient process of orbital forming can be used to manufacture functional components with a varying sheet thickness profile. It is characterized by a tumbling movement of the die and counterpunch, thus reducing the contact area between work piece and tool as well as the maximum forming force significantly. Within the project A1 of the Transregional Collaborative Research Centre (TCRC 73), the process of orbital forming has been investigated fundamentally. The control of the material flow to increase the maximum form filling could be identified as major challenge. The objective of this transfer project is the enlargement of the forming limits in comparison to conventional orbital forming by developing and applying tailor-made process and heat treatment strategies for industrial relevant steel and aluminum alloys. For the purpose of a transfer to industrial application, a demonstrator geometry with a varying sheet thickness profile is defined. Main aspects of the investigation are the resulting geometric and mechanic properties and the possibility to enlarge the forming limits. The final geometric shape is realized by applying different cutting operations. An industrial application is evaluated by assembling the demonstrator to a near-series clutch disc and analyzing the functional behavior.<br
Keywords: Sheet-Bulk Metal Forming; Orbital Forming; Material Flow Control